Impact of subgingival periodontal treatment on systemic markers of inflammation in patients with metabolic syndrome: a systematic review of randomized clinical trials - Chavez, Marie; Ramirez, Asshly; Hernández-Vásquez, Akram; Comandé, Daniel; Azañedo, Diego (Frontiers in Oral Health, 2025)
IntroductionThis study synthesizes evidence on the impact of subgingival periodontal treatment combined with antibiotics on reducing systemic inflammation markers—C-reactive protein (CRP), interleukins, and tumor necrosis factor-alpha (TNF-α)—in patients with metabolic syndrome (MS) and periodontal disease (PD), compared to supragingival periodontal treatment with placebo.MethodsRandomized clinical trials (RCTs) published in English, Spanish, or Portuguese that addressed the research question were included. A search was conducted in eight databases (PubMed, EMBASE, CINAHL, LILACS, Scopus, WoS Core Collection, Dentistry & Oral Science Source, and Cochrane Central) on June 20, 2023. Risk of bias was assessed using the Cochrane RoB 2 tool, and evidence certainty was evaluated following GRADE guidelines. A qualitative synthesis of the evidence was performed.ResultsTwo RCTs with 228 participants (ages 35–65) were included. Montero et al. reported significant reductions in CRP levels favoring the treatment group at 3 months (2.7 mg/L ± SE: 0.4 vs. 3.9 mg/L ± SE: 0.6; p = 0.001) and 6 months (2.9 mg/L ± SE: 0.4 vs. 4.0 mg/L ± SE: 0.8; p = 0.004). Lopez et al., however, found no significant differences throughout follow-up. Only Montero et al. reported on interleukin 1β and TNF-α, observing significant reductions at 3 months for interleukin 1β (0.9 pg/dl ± SE: 0.1 vs. 2.3 pg/dl ± SE: 0.5; p = 0.046) and TNF-α (6.4 pg/dl ± SE: 0.8 vs. 10.0 pg/dl ± SE: 2.3; p = 0.037).DiscussionThe evidence is limited by the small number of comparative RCTs. One RCT with low risk of bias demonstrated significant reductions in CRP, interleukins, and TNF-α levels at 3 months and CRP at 6 months. The other, with unclear risk of bias, showed no differences in CRP up to 12 months. Findings suggest that subgingival periodontal treatment with antibiotics reduces systemic inflammation for up to 6 months in patients with MS and PD. However, larger RCTs with standardized methods and longer follow-up are needed to confirm these results.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022366056, PROSPERO (CRD42022366056).